2017
DOI: 10.5935/1415-2762.20170004
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Terminal Kidney Disease in a State of Brazilian Amazonia

Abstract: RESUMOEsta pesquisa objetivou retratar o perfil sociodemográfico e clínico dos clientes em hemodiálise e os custos do tratamento dialítico no estado do Amapá. Trata-se de estudo transversal, com abordagem quantitativa. Os dados foram obtidos por meio do software Nefrodata e roteiro de entrevista estruturado, os quais foram analisados por meio de estatística descritiva. Foi sujeito da pesquisa a população em hemodiálise da Unidade de Nefrologia de Macapá. As prevalências sociodemográficas e clínicas constatadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…(25) Quanto à situação conjugal, observou-se maior percentual de pacientes casados (60%), resultado equivalente encontrado em outro estudo. (26) Perfil clínico dos pacientes renais crônicos em terapia renal substitutiva Em relação a doença de base, a Nefropatia Hipertensiva foi a principal etiologia encontrada, seguida da Nefropatia Diabética, dados semelhantes foram encontrados em nível nacional. (21) Observouse ainda, que 20% dos pacientes tinham outras causas (Lúpus Eritematoso Sistêmico, glomerulonefrite, neoplasia e Doença Cardiovascular).…”
Section: Discussionunclassified
“…(25) Quanto à situação conjugal, observou-se maior percentual de pacientes casados (60%), resultado equivalente encontrado em outro estudo. (26) Perfil clínico dos pacientes renais crônicos em terapia renal substitutiva Em relação a doença de base, a Nefropatia Hipertensiva foi a principal etiologia encontrada, seguida da Nefropatia Diabética, dados semelhantes foram encontrados em nível nacional. (21) Observouse ainda, que 20% dos pacientes tinham outras causas (Lúpus Eritematoso Sistêmico, glomerulonefrite, neoplasia e Doença Cardiovascular).…”
Section: Discussionunclassified
“…9,10 This result refers to the process of miscegenation present in the country, and consequently in health processes. 11 Other studies, in relation to schooling, identified from 4 to 8 years of study, and this low educational attainment hinders the treatment, since the degree of the patient's education influences the understanding about the disease and treatment, as well as the need for changing life habits. 2, 8,9 Most participants self-reported Catholics, as well as in other studies, in terms of religion.…”
Section: Introductionmentioning
confidence: 99%
“…8,12 This finding results from the fact that the country is predominantly Catholic, with 73.6% of the Brazilian population selfdeclared. 11 The time spent to perform hemodialysis could be described, as well as the form of admission to the treatment, in relation to the clinical characterization of patients. Regarding the time of hemodialysis, the result was similar to the literature, which records a period of 1 through 3 years of treatment 4,8,10 .…”
Section: Introductionmentioning
confidence: 99%